Factors predicting paediatric obesity among primary school children in Kuantan - Al-Mahmood, Sinan; Shamsuddin, Ariefah Hanim; Mohd. Saufi, Noor Amallina; Othman, Noratikah; Ibrahim, Wisam Nabeel (IIUM Press, 2018)
Objective: This study was aimed to investigate the association of parental obesity, food habits, and physical activity levels with body mass index status and sociodemographic factors among children in Kuantan, Pahang. Method: A cross-sectional study was conducted on 300 pupils in three primary schools in Kuantan. The three schools were representative of the three major ethnicities in Malaysia, Malays, Chinese, and Indians, and the children were aged 8 to 11 years. Self-developed questionnaires were used to record sociodemographic details and anthropometric measures of both parents and children, and physical activity and food habits were measured using a Children Physical Activity Questionnaire (C-PAQ) and the Harvard Food Frequency Questionnaire (HFFQ), respectively. Data was analysed using IBM SPSS 20.0, with a binary logistic regression model then used to represent the interactions among different factors in terms of predicting childhood obesity. Results: Binary logistic regression analysis shows that parental anthropometric measures, children’s ages, levels of physical activity, and food habits are signif-icant predictors for paediatric obesity. There is also a significant association between parents’ anthropo-metric measurements and childhood obesity. Significant correlation was found between fast food con-sumption, fruit and vegetable consumption, and physical activity and body mass index in children (p˂0.05). Conclusion: The study provides evidence that parental obesity, fast food consumption, fruit and vegetables intakes, and physical activity levels have significant associations with children's body mass indices.